Effect of Bacillus Subtilis Bacteria on The Mechanical Properties of Corroded Self-Healing Concrete (Fracture and Structural Integrity, 2024)
Reinforced concrete has a weakness for corrosion which can cause the concrete to crack and the concrete structure to fail. To overcome this problem, a self-healing concrete method is needed that can close cracks and inhibit the rate of natural corrosion. Bacillus subtilis as a self-healing agent in concrete has been proven to be able to increase the compressive strength and flexural strength of concrete. The method used in this research is to add bacterial hydrogel encapsulation to concrete with a variation of 0%; 0.1%; 0.6%; and 1.5% by weight of sand. The test object is a reinforced concrete beams and cylindrical concrete with compressive design strength of 30 MPa. The concrete specimens will go through a series of tests, such as corrosion acceleration tests using DC power supply, self-healing tests by visual observation, flexural strength, ductility, stiffness, and compressive strength tests using Universal Testing Machine (UTM). From the test results, it was found that the addition of 0.1% bacterial encapsulation variation was the optimum value for increasing the mechanical properties of self-healing concrete and reduce the corrosion rate on self-healing concrete.
Keywords: Self-Healing Concrete; Bacillus bacteria; Corrosion; Mechanical Properties; Reinforced Concrete